Emicizumab in two patients with acquired haemophilia A – case report - Zhao Milly; Kartika Thomas; Witenko Corey; Snead Jessica; DeSancho Maria T; Ciolek Alana (The Journal of Haemophilia Practice)
Patients with acquired haemophilia A (PwAHA) can present with severe bleeding and may require lengthy treatment with bypassing agents and immunosuppression. We present two cases of the implementation of emicizumab in PwAHA. The first patient, an 82-year-old man with rheumatoid arthritis (RA), presented with acquired haemophilia A (AHA) and spontaneous left tibia hematoma complicated by a persistent wound and infections. After a month of intermittent bleeding at the site and immunosuppression, the inhibitor level remained elevated and he was placed on emicizumab. While on therapy, debridement of the wound required activated factor VII therapy, which was complicated by a venous thromboembolism (VTE). He was successfully managed with anticoagulation while on emicizumab until his inhibitor level was undetectable. The second patient is a 62-year-old woman, also with RA and with a persistently positive dilute Russell viper venom time who presented with intracerebral haemorrhage (ICH) and was found to have AHA. After a period of time on bypassing agents, emicizumab was started due to a persistent inhibitor level and the ICH remained stable. She only required two doses initially, however, had a relapse with recurrent factor VIII inhibitor and received three additional doses without any complications. These cases highlight that emicizumab is a viable option in the care of PwAHA in challenging scenarios such as in the context of VTE and ICH.